Analisis Pengendalian Piutang Terhadap Resiko Piutang Tak Tertagih Pada PT Federal International Finance (FIF) Manado - Ruy, Yulita; Pelleng, Frendy A. O.; Manoppo, Wilfried S. (Sam Ratulangi University, 2018)
There are so many transactions the company conducts in its day-to-day activities. Starting from the activity of buying assets needed by the company, paying the various expenses required in order to obtain a benefit, until the activity of producing and selling certain products in order to survive, then every product produced must be sold to the public. In the control of accounts receivable is emphasized on the amount of receivables, credit and receivables receivable and policies run by the company. Such control measures shall be made prior to the delivery of the goods with the invoicing and expiration of the receivable collection. One of society's choice to get fund is through multi finance institution. One of the financing institutions operating in Manado City and its vicinity is PT Federal International Finance (FIF), which is able to provide funds to meet the needs of the community, which is also the object of my research. The purpose of this research is to know the control of accounts receivable against the risk of bad debts at the company. This research uses Quantitative Descriptive Analysis method. The data in search of this research is the control of receivables and the estimated amount of bad debts at PT Federal International Finance (FIF) Manado. From the details of the calculation of the age of receivables in 2016 and 2017, namely: Year 2016 has a prestige of = 1.1%, while the year 2017 of = 1.11%. This shows that the control of receivables at Manado's Federal International Finance (FIF) company is very good in the management of its receivables.